Pelatihan Penerapan Sistem Integrasi Data Kependudukan Sederhana (SIDaKS) Di Kecamatan Kota Agung Timur Tanggamus - Dani Al Mahkya; Fery Widhiatmoko; Dian Anggraini; Tirta Setiawan; Febri Dwi Irawati; Meida Cahyo Untoro (Jurnal Pengabdian kepada Masyarakat Radisi, 2022)
System-based data recording is indispensable in all fields, including government agencies. One of the important points in data recording is system integration. Data integration has the advantage of making the flow of organizational information better. One of the problems that arise in this Community Service activity partner is the unavailability of a population data integration system from each village/village to the sub-district. This activity aims to conduct training, mentoring and demonstration of the proposed integration system. The solution that will be offered is to conduct training and socialization related to population data management and integration. This training and socialization will use Ms. Excel and Google Sheet in the process. The method used in implementing community service activities is training and mentoring as well as demonstrations related to the Implementation of the Simple Population Data Integration System (SIDaKS) in Kota Agung Timur District, Tanggamus. The training was carried out in the East Kota Agung District hall, Tanggamus. Participants who attended the activity were representatives of each village/village in the Kota Agung Timur District. There are several steps taken to support the implementation of activities. The activity took place smoothly in accordance with the applicable health protocol. And it will be held on September 30, 2021 at the Kota Agung Timur , Tanggamus